Evidências do efeito do aquecimento global sobre a Reserva Extrativista Marinha (RESEX) do Delta do Parnaíba (PI) - Farias, Gabriela Aparecida Machado (2022)
Global warming is one of the effects of climate change, responsible for the increase in the average temperature of the atmosphere and oceans, acidification of the seas and changes in the coastal landscape. Considering the lack of information about this theme in the northeastern region of Brazil, 30 years (1990 to 2020) of images from Landsat 5 (TM) and Landsat 8 (OLI) satellites, SRTM interferometric radar and altimetric data were used to evaluate the possible effects of global warming on the Marine Extractive Reserve (RESEX) region of the Parnaíba Delta. The results indicate that the study area is experiencing an increase in mangrove areas accompanied by an expansion of the water surface, caused by environmental factors. The SRTM data of the study area corroborates with the mappings carried out, indicating a tendency of increase of the mangrove areas in the eastern portion of the RESEX. The thematic sensitivity map for mangrove expansion points out that areas close to water courses have a high level of vulnerability to mangrove expansion. Possibly the region is being subjected to an increasing saline intrusion, given that the portion adjacent to the delta is experiencing an increase in mean sea level of about 2.82 mm/year, which could imply severe impacts on biodiversity and the local economy.